2009
DOI: 10.1111/j.1654-109x.2009.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

How do management and restoration needs of mountain grasslands depend on moisture regime? Experimental study from north‐western Slovakia (Western Carpathians)

Abstract: Question: How does species composition change in traditionally managed meadows after mowing has ceased, and in abandoned meadows after re-introduction of mowing? Are there differences in the dynamics of dry and moderately wet meadows?Location: Za´zriva´-Plesˇiva´(19111 0 N, 49116 0 E), north-western Slovakia, western Carpathians.Methods: Pairs of experimental plots (mown and unmown) were established to replicate each combination of dry/wet and traditionally managed/abandoned meadows. Changes in species composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
1
20
1
1
Order By: Relevance
“…It can therefore be assumed that if this part were still traditionally managed, the vegetation would have a character similar to that of the lower part. This expectation was also confirmed by our previous study, in which the mown plots in the upper part were moving towards acquiring the species structure of the plots in the bottom part and the abandoned plots in the lower part towards the species structure of the plots in the upper part of the locality (Galvánek and Lepš 2009). …”
Section: Experimental Design and Samplingsupporting
confidence: 80%
“…It can therefore be assumed that if this part were still traditionally managed, the vegetation would have a character similar to that of the lower part. This expectation was also confirmed by our previous study, in which the mown plots in the upper part were moving towards acquiring the species structure of the plots in the bottom part and the abandoned plots in the lower part towards the species structure of the plots in the upper part of the locality (Galvánek and Lepš 2009). …”
Section: Experimental Design and Samplingsupporting
confidence: 80%
“…To preserve grasslands of high natural value, the impacts of the environmental factors should also be considered in addition to becoming acquainted with the history and present conditions of the landscape use [36,[46][47][48][49][50].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the vegetation inside the fence will change to an alternative state [24]. Galvánek and Lepš [3] showed that the species composition of the restored plots after the reintroduction of mowing was still far from the target composition. Therefore, different management methods are needed to ensure the correct succession pathways are followed for ecological restoration and to enhance colonization of the target species [34], rather than the restored site resulting in an alternative state [24].…”
Section: Resultsmentioning
confidence: 99%
“…However, most of these have been abandoned with changes in lifestyle and farming methods [2], as in other countries (e.g., [3]). In Japan, forests cover 78% of the land area [4] and the mild, humid climate promotes the growth of forests [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation